He Says, She Says: Mothers and Children Remembering the Same Events. Issue 6 (10th August 2017) - Wang, Qi; Song, Qingfang
Abstract : This study examined the consistency of memories for the same events in mothers and children, and how that varied as a function of culture and organizational components of memories. European American (EA) and Chinese immigrant (CI) mothers and their 6‐year‐old children ( N  =   127) independently recalled two emotionally salient events. In both cultures, mothers and children agreed more on factual event details and observable behaviors and less on subjective experiences and idiosyncratic interpretations. EA mothers and children told more diverse stories than did CI mothers and children. The findings shed important light on autobiographical memory as a multidimensional construct shaped by cultural beliefs and practices, and have critical implications for the evaluation of memory accuracy in research and real‐life settings.